2001
DOI: 10.1128/mcb.21.24.8483-8489.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Respiratory Electron Carriers Are Involved in Oxidative Stress during Heat Stress in Saccharomyces cerevisiae

Abstract: In the present study we sought to determine the source of heat-induced oxidative stress. We investigated the involvement of mitochondrial respiratory electron transport in post-diauxic-phase cells under conditions of lethal heat shock. Petite cells were thermosensitive, had increased nuclear mutation frequencies, and experienced elevated levels of oxidation of an intracellular probe following exposure to a temperature of 50°C. Cells with a deletion in COQ7 leading to a deficiency in coenzyme Q had a much more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(133 citation statements)
references
References 32 publications
6
123
3
1
Order By: Relevance
“…We observed the largest amount of phenotypic variance when cells were grown under high temperature stress (37°) and that mt-n epistasis explained a significant component of this phenotypic variance (Figure 4). In yeast, high temperature increases oxidative stress produced by the electron transport chain (Davidson and Schiestl 2001). We found that endogenous levels of ROS were influenced by mt-n interactions for a number of strains at high temperature ( Figure 7).…”
Section: Intraspecific Mt-n Epistasismentioning
confidence: 86%
“…We observed the largest amount of phenotypic variance when cells were grown under high temperature stress (37°) and that mt-n epistasis explained a significant component of this phenotypic variance (Figure 4). In yeast, high temperature increases oxidative stress produced by the electron transport chain (Davidson and Schiestl 2001). We found that endogenous levels of ROS were influenced by mt-n interactions for a number of strains at high temperature ( Figure 7).…”
Section: Intraspecific Mt-n Epistasismentioning
confidence: 86%
“…Trichophyton sp. was rich in mitochondria which was a target of oxidative stress 21 . Heat-stressed cells have been reported to exhibit increased sensitivity to low levels of chemicals including essential oils 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Heat-treated plants are also usually subjected to oxidative injuries as a result of an increased production of oxygen radicals in chloroplasts and mitochondria, and these organelles react by production of specific anti-stress proteins to eliminate unfavorable effects (Yordanov 1992;Davidson and Schiestl 2001;Silva et al 2010). Rizhsky et al (2002Rizhsky et al ( , 2004 reported increased levels of transcripts encoding reactive oxygen intermediate-detoxifying enzymes in the treated mitochondria.…”
mentioning
confidence: 99%